MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN METODE DISKUSI DI KELAS IV SDN 004 TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Desfita Desfita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This research is motivated by low learning result of IPS student, for that done research by applying method of discussion with aim to improve result of study of IPS student of SDN 004 Tembilahan Kabupaten Indragiri Hilir. This research is a classroom action research conducted two cycles. Research stage consists of four stages, namely: planning, implementation, observation and reflection. The result of research stated that: activity of teacher in cycle I 65,62% with enough category, and at meeting II 78,13% with good category. In the second cycle of meeting I was 84.36% with very good category, and at meeting II 90.62% with very good category. Student activity in the first cycle of meeting I 62.50% with enough category, and at the second meeting 75.00% with good category and on the second cycle of meeting I 84.36% with good category, and at meeting II get score 27 (84, 36%) with very good category. Student learning outcomes in the first cycle average student learning outcomes is 63.91 with a total number of students who totaled 17 students (53.13%). In the second cycle average student learning outcomes is 74.69 with a total number of students who totaled 26 students (81.25%). Based on the results of this study can be concluded that the implementation of discussion methods can improve student learning outcomes IPS.